Harmonic Scalpel Compared to Conventional Hemostasis in Thyroid Surgery: A Meta-Analysis of Randomized Clinical Trials. (16th February 2010) - Melck, Adrienne L.; Wiseman, Sam M.
Abstract : Background . The study's aim was to determine whether conventional hemostasis (CH) or the Harmonic Scalpel (HS) results in shorter operative times for thyroidectomy and to evaluate the incidence of postoperative complications with each approach. Methods . A literature search was conducted from study inception to September 30, 2008. Included studies randomized thyroidectomy patients to either CH or HS and reported the incidence of postoperative transient recurrent laryngeal nerve dysfunction (RLND) and hypocalcemia. Results . Nine RCTs were included. Use of the HS reduced operative time by 23.1 minutes (95% CI = 13.8, 32.33). There was no difference in the incidence of transient RLND (RR = 1.25, 95% CI = .56, 2.76), but a lower rate of transient hypocalcemia with the use of the HS (RR = .69, 95% CI = .51, .92). Conclusions . The use of HS in thyroidectomy significantly reduces operative time and is associated with a reduction in postoperative hypocalcemia compared to CH.